THE EFFECT OF INFLATION AND EDUCATION LEVEL ON PER CAPITA EXPENDITURE IN NORTH SUMATRA - Siti Rabiah; Reza Juanda; Murtala; Hijri Juliansyah (LPPM Universitas Malikussaleh, 2025)
This study aims to determine the effect of inflation and the level of education on per capita expenditure in North Sumatra in 2004-2023. The research method used in this study is a multiple linear regression method. The results of this study indicate that partially the inflation rate has no effect on per capita expenditure in North Sumatra. While the level of education has a positive and significant effect on per capita expenditure in North Sumatra. Simultaneously showed that the rate of inflation and the level of education affect per capita spending in North Sumatra.